Energetic efficiency and temperature sensitivity of soil heterotrophic respiration vary with decadal-scale fire history in a wet sclerophyll forest. (July 2019) - Butler, Orpheus M.; Lewis, Tom; Rashti, Mehran Rezaei; Chen, Chengrong
Abstract: Changes in fire regime and soil temperatures will be simultaneous symptoms of climate change in many regions around the world, yet very few studies have investigated how these factors will interact to affect soil carbon (C) cycling. Interacting effects of fire regime and temperature on soil C cycling processes might constitute an important but poorly-understood feedback to the global climate system. Using soils from one of the world's longest running prescribed fire trials in eastern Australia, we investigated the effect of fire regime on the rate, energetic efficiency, and temperature sensitivity of soil heterotrophic respiration and associated properties across a range of incubation temperatures (15 °C, 25 °C, and 35 °C). Levels of total, labile, soluble, and microbial biomass C were 32%, 59%, 64%, and 38% lower, respectively, in biennially-burned (2yB) soils than in soils that had not been exposed to fire since 1969 (NB soils). Moreover, while rates of heterotrophic respiration did not vary among NB, 2yB or quadrennially-burned (4yB) soils during the 55-day incubation period, values of q CO2 (which are inversely related to microbial energetic efficiency) were 59.8% higher in 2yB soils than in NB soils. This suggests that biennial-burning is associated with soil conditions that promote energetic inefficiency in the microbial community and highlights the role of environmental stress as a determinant of respiratory responses to fire regime. Respiration temperature sensitivity (i.e. Q 10 values) of 2yB soils was 86% greater than that of 4yB soils at the temperature range of 15–25 °C. This effect was absent at the temperature range of 25–35 °C and in soils to which labile C levels had been boosted through glucose addition. This pattern in Q 10 values might be attributed to low quality soil organic matter in 2yB soils in combination with mechanisms associated with microbial community structure. Together these results enhance our understanding of C cycling in fire-affected soils and suggest a potentially important positive feedback between fire, climate change, and the terrestrial C cycle that warrants further investigation. Highlights: Biennially-burned (2 yB) soils had lower levels of carbon than unburned (NB) soils. Energetic efficiency of microbial biomass was lower in 2 yB than NB soils. Overall rates of heterotrophic CO2 respiration were not affected by fire regime. Fire regime affected respiration temperature sensitivity between 15 and 25 °C. Temperature and fire regime interacted to affect microbial biomass stoichiometry.